(untitled) (Research, Society and Development, 2022)
The growth of the elderly population results in an increasing demand for health services, considering that the rates of hospitalizations and the duration of hospitalizations increase with age, generating important economic repercussions. A problem faced is the increase in the number of cases in the elderly due to fracture of the femur, generating a high cost for the Unified Health System. This study proposes to analyze the total number of expenses related to hospitalizations for femoral fractures, from an age perspective, in Brazil, between 2016 and 2020. This is an epidemiological, retrospective and quantitative study carried out using secondary data. The costs of hospitalizations for fractures of the femur in the elderly were analyzed between 2016 and 2020 in Brazil, based on the investigation of the variables average and total cost per hospitalization, as well as region. In the analyzed period, 291,369 hospitalizations for fracture of the femur were registered, in people between 60 and 80 years old or more, in Brazil. With regard to geographic regions, the largest number of hospitalizations is concentrated in the Southeast region, with 150,547 cases. Regarding age group, patients over 80 years old were the most affected, representing a total of 140,155 cases. Regarding biological gender, females predominated, totaling 198,472 admissions. Therefore, it is noted that this issue represents a major impact on public health, which is related to high socioeconomic costs.